Transformational Leadership as a Strategy for Internalizing Integrity: A Study at Nuurul Fikri Integrated Islamic Elementary School - Nurul Rofiyatul Latifah; Ikmi Nur Oktavianti; Enung Hasanah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Good leadership is determined by the extent to which a principal is able to serve as a role model of integrity for the entire school community, because the effectiveness of education cannot be measured solely by academic achievement, but also by a leader’s ability to instill the value of honesty through consistent, tangible behavior. This study aims to analyze the role of transformational leadership based on the principal’s exemplary conduct as a strategy for internalizing the value of integrity in an integrated Islamic elementary school. The study employs a qualitative approach using a case study design to gain an in-depth understanding of the process of internalizing character values as it naturally unfolds in the field. Research participants were selected through purposive sampling, including the principal, vice principal, homeroom teachers, students, and parents, with the study conducted at SDIT Nuurul Fikri in Trenggalek, East Java. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, which were then reinforced through source triangulation and methodological triangulation to ensure the validity of the research findings. The main results of the study indicate that the process of internalizing the value of integrity occurs through three mutually reinforcing dimensions: the knowing the good aspect, rooted in the prophetic example of the Prophet Muhammad’s siddiq character; the feeling the good” aspect, which holds that honesty must begin with leaders; and the “acting the good” aspect, achieved through habitual practice.